The urbanization of the neighborhood of the ’Magdalena’, Mr. ’Bernardino de Mendoza’, Captain General of the galleys of Spain, and other things (Granada, 1544-1551) - Porras Arboledas, Pedro Andrés (Cuadernos de Historia del Derecho, 2020)
A documentary contribution of more than 500 transcribed letters and regesta of others taken from the protocols of the city of Granada during the years 1544-1551, showing the urbanization process that was taking place in the Arenal suburb, transformed after the Christian conquest in the neighborhood of La Magdalena, a neighborhood specialized in lodging, road work, restaurants, transport of wood, supply of manure, production of horticultural products and all the imaginable range of trades that these economic sectors needed. It starts from the subdivision of the orchard that Mr. Bernardino de Mendoza, Captain General of the galleys of Spain, had there, whose plots were handed over against the constitution of the corresponding emphyteutical censuses.